Avaliação da expressão da enzima ácido graxo sintase (FASN) em carcinomas de glândulas salivares - Angelis, Camila Matsunaga de, 1986- (2019)
Orientadores: Fernanda Viviane Mariano Brum Correa, Albina Messias de Almeida Milani Altemani